Evaluation ofthe effectiveness of information technology outsourcing - Nazarenko, S. M.; Pererva, P. G. (My University, 2023)
It has been proven that the main source of the economic effect of outsourcing when using IT outsourcing is an increase in the level of efficiency of the industrial enterprise as a whole, as well as the possibility of releasing the relevant organizational, financial and personnel resources for the development of new directions.
Оцінка ефективності аутсорсингу інформаційних технологій
Keywords: information technologies; outsourcing; services; efficiency; enterprises